Diffusive and Metabolic Constraints to Photosynthesis in Quinoa during Drought and Salt Stress - Killi, Dilek; Haworth, Matthew (Plants (Basel), 2017)
Quinoa (Chenopodium quinoa Willd.) has been proposed as a hardy alternative to traditional grain crops in areas with warm-to-hot climates that are likely to experience increased drought and salt stress in the future. We characterised the diffusive and metabolic limitations to photosynthesis in quinoa exposed to drought and salt stress in isolation and combination. Drought-induced pronounced stomatal and mesophyll limitations to CO2 transport, but quinoa retained photosynthetic capacity and photosystem II (PSII) performance. Saline water (300 mmol NaCl-equivalent to 60% of the salinity of sea-water) supplied in identical volumes to the irrigation received by the control and drought treatments induced similar reductions in stomatal and mesophyll conductance, but also reduced carboxylation of ribulose-1,5-bisphosphate carboxylase/oxygenase, regeneration of ribulose-1,5-bisphosphate, increased non-photochemical dissipation of energy as heat and impaired PSII electron transport. This suggests that ion toxicity reduced PN via interference with photosynthetic enzymes and degradation of pigment–protein complexes within the thylakoid membranes. The results of this study demonstrate that the photosynthetic physiology of quinoa is resistant to the effects of drought, but quinoa may not be a suitable crop for areas subject to strong salt stress or irrigation with a concentration of saline water equivalent to a 300 mmol NaCl solution.